Telaah Pemikiran KH Mohammad Hasan Genggong sebagai Ulama’, Mursyid, Pejuang dan Teladan Bangsa - Qosim, Nanang; Hamid, Abdul (SETYAKI : Jurnal Studi Keagamaan Islam, 2024)
KH Mohammad Hasan Genggong is a scholar who holds the title "Al-'Alim-al-'Allamah", charismatic, productive, highly dedicated to national civilization and respected by the government and all levels of society. A figure like him has a generous nature towards the ummah. KH. Mohammad Hasan is known as a man who loves knowledge, is intelligent, qonaah, honest, has a high memorization capacity so he can easily study with his teachers. One of the teachers is; KH. Syamsuddin, KH. Rofi'I Sentong Kraksaaan, KH. Mohammad Tamrin Sukonsari Pasuruan, KH. Moh. Cholil Bangkalan. He has several spectacular works in the form of yellow books including; Aqidah al-Tauhid fi Ilmi al-Tauhid, Nadlam Safinah al-Najah fi al-Fiqhi, Al-Ahadits al-Nabawiyyah 'Ala Tartib al-Akhruf al Hijaiyyah, Khutbatain Li 'Id al-Fitri wa Adha, Khutbatain al-Nikah, Friday Sermon, and Al-syi'ru Bi Lughah al-Manduriyyah. Kiai's thought contributions include being part of the spirit of the founding of the Nahdlatul Ulama Organization, Mursyid Tarekat Naqsyabandiyah Ali Ba'alawiyah, and the initiator and driving force of the Indonesian independence struggle.